Prenatal screening of gestation. Complementary tests in the diagnosis and management of pregnancy. - Viacava Meléndez, Manuel (2015)
Since the first control pregnant, requested laboratory tests. The dosage of hemoglobin and hematocrit were monitored in the 6th month and in late pregnancy; These tests allow us to detect various types of anemia.